Slow integrin-dependent migration organizes networks of tissue-resident mast cells - Kaltenbach, Lukas; Martzloff, Paloma; Bambach, Sarah K.; Aizarani, Nadim; Mihlan, Michael; Gavrilov, Alina; Glaser, Katharina M.; Stecher, Manuel; Thünauer, Roland; Thiriot, Aude; Heger, Klaus; Kierdorf, Katrin; et al. (Nature immunology, 2023)
Immune cell locomotion is associated with amoeboid migration, a flexible mode of movement, which depends on rapid cycles of actin polymerization and actomyosin contraction1. Many immune cells do not necessarily require integrins, the major family of adhesion receptors in mammals, to move productively through three-dimensional tissue spaces2,3. Instead, they can use alternative strategies to transmit their actin-driven forces to the substrate, explaining their migratory adaptation to changing external environments. However, whether these generalized concepts apply to all immune cells is unclear. Here, we show that the movement of mast cells (immune cells with important roles during allergy and anaphylaxis) differs fundamentally from the widely applied paradigm of interstitial immune cell migration. We identify a crucial role for integrin-dependent adhesion in controlling mast cell movement and localization to anatomical niches rich in KIT ligand, the major mast cell growth and survival factor. Our findings show that substrate-dependent haptokinesis is an important mechanism for the tissue organization of resident immune cells.